Wilm’s tumor relapses in children were treated in Department of Children Surgery - Kowalski, Janusz; Madziara, Wojciech (Przewodnik Lekarza/Guide for GPs, 2005)
From 1992 to 2003 year in the Department of Children Surgery in Katowice were undergoing a treatment of 108 children with Wilm’s tumor in age between 6 month and 16 years. In 8 patients (7.4%) there were diagnosed another malignant neoplasm different from Wilm’s tumor. Stage at diagnosis was following as: 12 – I, 35 – N/-/, 4 – N/+/, 30 – III, 4 – IV and 1 – V. In 23.2% was recognized high risk histopathology of tumor and 3.5% a low risk and 73.3% a standard type of histology. About 11 patients (12.8%) had relapses of Wilm’s tumor and all of them were treated by chemotherapy for relapses with surgical removed metastases by thoracotomy in 5 cases. There were 8 cases of death: 5 complications during the chemotherapy and 3 cases without response for treatment.